Analisis Akurasi Peramalan Menggunakan Metode Fuzzy Time Series Lee - Mardianto, Arief; Muflihah, Nur; Mayasari, Andhika; Nuning Farida Afiatna, Fatma Ayu (INVANTRI (Inovasi Dan Pengelolaan Industri), 2024)
Gema Frozen is a company that sells and distributes frozen food products such as sausages, nuggets, corned beef and many other products. Every month, sales of Gema Frozen frozen food products continue to experience a significant increase in the market. This phenomenon causes the company to face demand overload caused by the increase in sales, to anticipate the occurrence of overload, forecasting is needed. By using Lee's fuzzy time series method, the purpose of this study is to analyze product sales forecasting and sales forecasting accuracy. This method is derived from time series analysis that utilizes fuzzy logic and uses fuzzy sets as the basis for its calculations. The results of forecasting analysis using this method resulted in an average difference between sales data and forecasting data of 3.65. This method's forecasting accuracy level is calculated, and the result is an MAE of 55.856. The MSE is 6029.641. -9.97% MPE and 33.78% MAPE values. The Lee approach performs well in predicting, according to the computation of forecasting accuracy.